Numerical benchmark of transient pressure-driven metallic melt flows. (December 2020) - Vignitchouk, L.; Khodak, A.; Ratynskaia, S.; Kaganovich, I.D.
Abstract: Fluid dynamics simulations of melting and crater formation at the surface of a copper cathode exposed to high plasma heat fluxes and pressure gradients are presented. The predicted deformations of the free surface and the temperature evolution inside the metal are benchmarked against previously published simulations. Despite the physical model being entirely hydrodynamic and ignoring a variety of plasma–surface interaction processes, the results are also shown to be remarkably consistent with the predictions of more advanced models, as well as experimental data. This provides a sound basis for future applications of similar models to studies of transient surface melting and droplet ejection from metallic plasma-facing components after disruptions. Highlights: Fluid simulations of cathode spots in vacuum arcs are benchmarked against published results. The cathode temperature response and surface deformation are well reproduced. Droplet ejection is predicted with similar characteristics to those measured in experiments.